A spectroscopic method for quick evaluation of tint strength and tint tone of titania (rutile) pigment and factors affecting them. Issue 1 (23rd October 2018) - Sharafudeen, Riyas
Abstract: Titanium dioxide (TiO2 ) manufacturing industries measure optical properties such as brightness, colour, tint strength, tint tone, gloss, scatter coefficient, and others to ensure the quality of the product. Product characterization and process control generally focus on the optical properties, which determine its quality. In this work, titania rutile pigment with varying tint strength and tint tone is analyzed and a correlation is established between particle size and the optical properties such as tint strength and tint tone. It is observed that optical properties of titania pigment depends on the particle size as well as particle size distribution. A relatively faster evaluation of tint strength and tint tone can be made using the reflectance and particle size measurements. Analytical samples were prepared by ultrasonic dispersion of pigment in water containing calgon as dispersing agent. To verify the accuracy of the method, pigment tint strength and tint tone obtained from this study are compared with those resulting from traditional analysis. The results showed that the new method is viable.